Limited Impact of Subglacial Supercooling Freeze-on for Greenland Ice Sheet Stratigraphy - Dow, Christine F.; Karlsson, Nanna B.; Werder, Mauro; id_orcid:0 000-0003-0137-9377 (Geophysical Research Letters, 2018)
ISSN:0094-8276 ISSN:1944-8007